2019
DOI: 10.1111/jvh.13096
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death among persons diagnosed with hepatitis C infection in the pre‐ and post‐DAA era in England: A record linkage study

Abstract: Summary Through record linkage, we describe the causes of death among persons with diagnosis of hepatitis C virus (HCV) in England. Persons ≥1 year with anti‐HCV/HCV‐PCR tests reported to PHE sentinel surveillance during 2002‐2016 were linked to death registrations from the Office for National Statistics during 2008‐2016. We found that 8.6% of the 204 265 with evidence of HCV during the study period died. Among them, external causes (accidental poisoning from drugs) and liver disease (end‐stage liver disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Similar results have been found in Italy, the United States (US) and Argentina [9-11]. A declining contribution of HCV-associated cirrhosis and cancer to transplants is helpful but is not a substitute for monitoring rates of HCV-associated transplants and may be limited by under-reporting of HCV coding in the liver transplant dataset, as has been observed in death registry data [12].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results have been found in Italy, the United States (US) and Argentina [9-11]. A declining contribution of HCV-associated cirrhosis and cancer to transplants is helpful but is not a substitute for monitoring rates of HCV-associated transplants and may be limited by under-reporting of HCV coding in the liver transplant dataset, as has been observed in death registry data [12].…”
Section: Introductionsupporting
confidence: 65%
“…It is important to note that under-reporting of HCV-associated transplants is minimal, with only 3.2% of linked individuals having no record of HCV-associated disease or positive HCV tests in the transplant registry. This is much lower than the under-reporting with HCV-associated mortality in England, where 41% of persons who died of liver-related causes linked to an HCV laboratory diagnosis did not have HCV recorded as a contributory cause in the deaths registry [12]. A similar level of under-reporting in mortality was also identified in the US [25] and Scotland [26], with 41% and 52% of individuals who died of liver-related causes, respectively, having HCV indicated on their death certificate.…”
Section: Discussionmentioning
confidence: 99%
“…The expected decrease in mortality due to DAA is not occurring, or more probably not yet observable. Indeed, some studies have reported a decline in mortality after the introduction of DAA, but only from 2016 onwards [ 13 ]. As data for wider use of DAA were only available for 3 years (2014–2016), a period when prescription of DAA in Switzerland was limited based on fibrosis stage [ 24–26 ], we were not able to evaluate the difference between successful IFN treatment and successful DAA treatment regarding liver-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few studies have analyzed detailed patterns of cause-specific mortality among HCV-infected persons [ 12 , 13 ]. We therefore investigated the risk factors and time trends for all-cause and cause-specific mortality among HCV-infected persons in the SCCS.…”
mentioning
confidence: 99%
“…The significance of confounding factors is clearly exemplified in a recent study by the same group where the median age of death was lower in persons with evidence of HCV than the general population (53 years vs 81 years). A significant proportion of persons with HCV died of external causes, liver disease and HIV compared to the general population[ 153 ].…”
Section: Hcv Infection: How Dangerous Is It Really?mentioning
confidence: 99%